Nanotherapeutics in autophagy: a paradigm shift in cancer treatment - Negi S.; Chaudhuri A.; Kumar D.N.; Dehari D.; Singh S.; Agrawal A.K. (My University, 2025)
Autophagy is a catabolic process in which an organism responds to its nutrient or metabolic emergencies. It involves the degradation of cytoplasmic proteins and organelles by forming double-membrane vesicles called “autophagosomes.” They sequester cargoes, leading them to degradation in the lysosomes. Although autophagy acts as a protective mechanism for maintaining homeostasis through cellular recycling, it is ostensibly a cause of certain cancers, but a cure for others. In other words, insufficient autophagy, due to genetic or cellular dysfunctions, can lead to tumorigenesis. However, many autophagy modulators are developed for cancer therapy. Diverse nanoparticles have been documented to induce autophagy. Also, the highly stable nanoparticles show blockage to autophagic flux. In this review, we revealed a general mechanism by which autophagy can be induced or blocked via nanoparticles as well as several studies recently performed to prove the stated fact. In addition, we have also elucidated the paradoxical roles of autophagy in cancer and how their differential role at different stages of various cancers can affect its treatment outcomes. And finally, we summarize the breakthroughs in cancer disease treatments by using metallic, polymeric, and liposomal nanoparticles as potent autophagy modulators. Graphical abstract: [Figure not available: see fulltext.] © 2022, Controlled Release Society.